ANALYTICAL MODEL OF ENERGY DETERMINATION VERTICAL VIBRATIONS WITH MULTI-NUMBER AND MULTI-LEVEL DAMPING OF MOBILE MACHINES ACCOUNTING FOR ROAD IRREGULARITIES (Journal of Universal Science Research, 2024)
The results of theoretical studies of multi-numerical and multi-level damping, as well as the influence of the relaxation element on the vibration-protective properties of the suspension of mobile vehicles, are presented. The vertical vibrations of mobile machines with multi-numerical and multi-level damping and on a relaxation damper were mathematically modeled. The damping of the main parts of a wheeled tractor was analytically determined, and the damping of the main parts of a multi-row relaxation wheeled tractor was also analytically determined.